Influence of plasticizers on the rheology and early heat of hydration of blended cements with high content of fly ash. (January 2016) - Ng, S.; Justnes, H.
Abstract: The dispersing effectiveness of five commercial plasticizers; lignosulfonate (LS), naphthalene sulphonate–formaldehyde polycondensate (NSF) and three polycarboxylate ethers (PCEs) were quantitatively investigated in blended cements where ordinary portland cement (OPC) was partly replaced by fly ash (FA) up to 60%. The capacity of the plasticizers in FA blended cements mimics that in the OPC system. At low replacement amounts, FA acts mainly as filler and does not impart any significant effect on the plasticizers. From 40% FA loading, PCEs showed decreased performance compared to NSF and LS relative to that in OPC systems, attributing to higher affinity of the latter polymers for cement clinkers. Retardation by plasticizers is more pronounced at higher FA contents due to lower adsorption on FA than on cement grains. Performance of plasticizers in industrial FA blended cements mimics that in OPC due to its relative higher surface area to compensate otherwise lower early strength.